2022
DOI: 10.33448/rsd-v11i1.24531
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of the Chronological Dental Mineralization Table of Permanent Teeth among Brazilians in the city of Belo Horizonte

Abstract: The knowledge of an individual age, especially children and young people, is  important in civil and criminal cases, such as adoption and when is important determining criminal imputability. To estimate this age, when there are no suitable documents to prove it, body development factors are used, especially those that show the stages of mineralization of the teeth. To this estimation, numerous tables have been developed in the most diverse regions. The aim of this study was to analyze the accuracy of the Chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For the Brazilian population, the use of the N.M.M. table [ 17 ] has presented low success rates [ 16 , 18 , 19 ], as well as methods based on foreign populations [ 19 , 20 ]. Authors have demonstrated the need to obtain current data on dental mineralization stages in Brazilian individuals [ 2 , 19 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the Brazilian population, the use of the N.M.M. table [ 17 ] has presented low success rates [ 16 , 18 , 19 ], as well as methods based on foreign populations [ 19 , 20 ]. Authors have demonstrated the need to obtain current data on dental mineralization stages in Brazilian individuals [ 2 , 19 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Niquini et al [ 19 ] performed a study to determine the accuracy of the chronological table of mineralization of permanent teeth among Brazilians. The authors used 442 panoramic radiographs of individuals aged between 5 and 30 years and 4 months taken in the downtown area of the city of Belo Horizonte-MG, Brazil, applying the Brazilian N.M.M.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations